Coaching the coach: A randomized controlled study of a novel curriculum for procedural coaching during intubation. Issue 2 (14th March 2023) - Miller, Kelsey A.; Auerbach, Marc; Bin, Steven S.; Donoghue, Aaron; Kerrey, Benjamin T.; Mittiga, Matthew R.; D'Ambrosi, Gabrielle; Monuteaux, Michael C.; Marchese, Ashley; Nagler, Joshua
Abstract: Background: Videolaryngoscopy allows real‐time procedural coaching during intubation. This study sought to develop and assess an online curriculum to train pediatric emergency medicine attending physicians to deliver procedural coaching during intubation. Methods: Curriculum development consisted of semistructured interviews with 12 pediatric emergency medicine attendings with varying levels of airway expertise analyzed using a constructivist grounded theory approach. Following development, the curriculum was implemented and assessed through a multicenter randomized controlled trial enrolling participants in one of three cohorts: the coaching module, unnarrated video recordings of intubations, and a module on ventilator management. Participants completed identical pre and post assessments asking them to select the correct coaching feedback and provided reactions for qualitative thematic analysis. Results: Content from interviews was synthesized into a video‐enhanced 15‐min online coaching module illustrating proper technique for intubation and strategies for procedural coaching. Eighty‐seven of 104 randomized physicians enrolled in the curriculum; 83 completed the pre and post assessments (80%). The total percentage correct did not differ between pre and post assessments for any cohort. Participants receiving the coaching module demonstrated improved performance on patient preparation, made more suggestions for improvement, and experienced a greater increase in confidence in procedural coaching. Qualitative analysis identified multiple benefits of the module, revealed that exposure to video recordings without narration is insufficient, and identified feedback on suggestions for improvement as an opportunity for deliberate practice. Conclusions: This study leveraged clinical and educational digital technology to develop a curriculum dedicated to the content expertise and coaching skills needed to provide feedback during intubations performed with videolaryngoscopy. This brief curriculum changed behavior in simulated coaching scenarios but would benefit from additional support for deliberate practice.